Linguistic Landscape of Tbilisi: a Case Study of Graffiti - Radavičiūtė, Jūratė (Respectus Philologicus, 2017)
The article investigates graffiti of Tbilisi, Georgia, as a part of the linguistic landscape of the city. The research is carried out within the theoretical framework of linguistic landscape, based on the works by Landry and Bourhis (1997), Gorter (2006), Jaworski and Thurlow (2010), etc. The aspects of multimodality, multilingualism and sociality are focused on in the research. The graffiti analysed displays the features of multimodality where visual images are used alongside with written texts, thus, adding the element of complexity to the discourse investigated. It must be pointed out that the use of English language for graffiti making prevails. Regarding the social aspect of the linguistic landscape, Tbilisi graffiti shows the engagement of street artists in a socially-relevant discussion tackling both local and state-level problems. The display of Tbilisi graffiti demonstrates the fluidity of this type of narrative: older graffiti are covered with new ones in addition to being cleaned or covered with official or commercial signage.